2001
DOI: 10.1159/000048710
|View full text |Cite
|
Sign up to set email alerts
|

Transdifferentiation of Pigmented Epithelial Cells: A Source of Retinal Stem Cells?

Abstract: In urodeles, larval anurans, embryonic chicks and rodents, the retinal pigmented epithelium (RPE) is capable of transdifferentiation and generating new neurons. Recent evidence suggests that pigmented cells in the ciliary body of the adult rodent eye are capable of producing new neurons in vitro. Here we provide data to suggest that the pigmented epithelium at the retinal margin of postnatal chickens is similar to that found in the embryonic retina. Pigmented cells at the retinal margin expressed mitf and pax6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 61 publications
4
46
0
Order By: Relevance
“…It was previously reported that CE-derived spheres express Nestin, a gene found in neural progenitor and stem cells (12). Our real-time RT-PCR analysis confirmed these previous findings (Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…It was previously reported that CE-derived spheres express Nestin, a gene found in neural progenitor and stem cells (12). Our real-time RT-PCR analysis confirmed these previous findings (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Thus, we propose that these cells can initiate transdifferentiation or reprogramming from pigmented CE cells rather than differentiate from RSCs or progenitors. This model is consistent with previous studies showing robust transdifferentiation between CE, retina, and retinal pigment epithelium in various species (10)(11)(12)(13)(14). To test this hypothesis, we maintained spheres on laminin-coated coverslips for 21 days, as described in refs.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Retinoblasts divide in the CMZ and as they are incorporated more centrally, they turn on genes that specify their particular retinal fates (Perron et al, 1998). Recent studies have shown that the most peripheral RPE at the rim of the optic cup has cells that continue to divide postnatally in chick (Fischer and Reh, 2001). This peripheral RPE, with the overlying choroid and underlying nonpigmented epithelium, generates the ciliary body and the iris near the anterior pole of the eye.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that some of the proliferating cells transfected with viruses were derived from the pigmented epithelium. However, there is no evidence that mature pigmented cells underlying central regions of the postnatal chick retina are capable transdifferentiating like the pigmented cells of early-stage chick embryos (for reviews, see Reh and Fischer, 2001;Fischer and Reh, 2001b). 6.…”
Section: Discussionmentioning
confidence: 99%